Chairman's Letter: Does it Communicate Something? - Bhuyan, Aswini Kumar; Baid, Devesh (Indian Journal of Finance, 2020)
Accounting narratives offer a very rich and complex set of inscriptions and represent a distinct genre of business communications. This study focused on Chairman's letter, which is a voluntary accounting narrative provided in most annual reports across the globe. Techniques of tone measurement and readability analysis were used to study Chairman's letter. Also, association of tone and readability with financial performance measures (stock return, return on equity, and return on assets) was assessed. The Henry wordlist was used to capture the tone and content of financial disclosures. Based on annual stock returns, top performing 50 companies and least performing 50 companies were drawn from NSE Nifty 500 list. Data were collected from the Bloomberg database. CAT scanner, QDA MinorLite, and SPSS software were used for analysis. The findings suggested that the Chairman's letter tone was positive and there was a significant difference between the tones of top performing and least performing companies. The readability analysis suggested that the Chairman's letter had a graduate-level readability. This level was above the danger line of difficulty; so, it should be made simple for the public to read. The correlation of tone and readability with performance measures was found to be significant.